1971
DOI: 10.1099/00221287-65-3-291
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Characterization of Acid and Alkaline Phosphatase in Yeast

Abstract: SUMMARYThe activity of acid and alkaline phosphatase in baker's yeast is derepressed when the organisms are starved of phosphate. Mutants lacking phosphatase activity and mutants with constitutive phosphatase synthesis were isolated. In all of them acid and alkaline phosphatases were affected simultaneously. Nevertheless, characterization of these two enzymes by sensitivity to inhibition by orthophosphate, temperature inactivation, proteolytic digestion and cation dependence showed that they were clearly disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
45
1

Year Published

1972
1972
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 27 publications
2
45
1
Order By: Relevance
“…The repressible alkaline phosphatase (namely, the nonspecific alkaline phosphatase) shows, however, a significant level of activity even under repressed conditions. This basal activity was found to be severely reduced in a pho8 (formerly phoH) mutant, and the enzyme failed to be derepressed.Repression or derepression of the repressible alkaline phosphatase occurs in response to signals of the presence or absence of inorganic phosphate in the medium (16,20,23). The signals are transmitted by the function of a regulatory system specified by the PHO4 (formerly PHOD), PHO80 (PHOR), PHO81 (PHOS), and PHO85 (PHOU) genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The repressible alkaline phosphatase (namely, the nonspecific alkaline phosphatase) shows, however, a significant level of activity even under repressed conditions. This basal activity was found to be severely reduced in a pho8 (formerly phoH) mutant, and the enzyme failed to be derepressed.Repression or derepression of the repressible alkaline phosphatase occurs in response to signals of the presence or absence of inorganic phosphate in the medium (16,20,23). The signals are transmitted by the function of a regulatory system specified by the PHO4 (formerly PHOD), PHO80 (PHOR), PHO81 (PHOS), and PHO85 (PHOU) genes.…”
mentioning
confidence: 99%
“…Repression or derepression of the repressible alkaline phosphatase occurs in response to signals of the presence or absence of inorganic phosphate in the medium (16,20,23). The signals are transmitted by the function of a regulatory system specified by the PHO4 (formerly PHOD), PHO80 (PHOR), PHO81 (PHOS), and PHO85 (PHOU) genes.…”
mentioning
confidence: 99%
“…The repressible APase is expressed only when the cells are starved for phosphate (14,22), whereas the so-called constitutive enzyme was recently shown to be synthesized only in the presence of phosphate (13). Extensive genetic analysis has revealed unlinked genes for several regulatory elements involved in APase repression and induction (20)(21)(22) …”
mentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae synthesizes several phosphatases involved in phosphorous metabolism (14). Two types of acid phosphatase (APase) (orthophosphoric-monoester phosphohydrolase [acid optimum]; EC 3.1.3.2) have been identified (22), one apparently produced constitutively and one repressed by Pi.…”
mentioning
confidence: 99%
“…It has been recently reported (Schurr & Yagil, 1971) that KH2P04 inhibits competitively yeast acid phosphatase. Kinetic studies performed in our laboratory revealed that KH,PO, is a competitive inhibitor of acid phosphatase in the living cells of commercial baker's yeast and in a cell-free extract, with a Ki value of 2.4 x I O -~ M. In our experiments total inhibition was achieved with 0-I M-KH,PO,.…”
mentioning
confidence: 99%